Church-State Relationship and Democratic Transition: A Comparative Study of Chile, Brazil, Spain and Poland - Natkaniec, Bozena (My University, 2003)
The main objective of this thesis is to examine the role of the Catholic Church in transition to democracy in Chile, Brazil, Spain and Poland. The main question under examination is whether the Catholic Church in these countries promoted or impeded the process of democratic conversion and consolidation. In an attempt to measure the Church's political influence during and following the democratic transformation four variables were examined. The selected variables were: abortion, divorce, education and constitutional amendments. The analysis revealed that the extent to which the Catholic hierarchy was able to impact these issues depended on the local context in each state. However, the main conclusion that can be reached is that the Catholic Church does not pose a serious obstacle to further consolidation of democracy in each of the countries examined. Moreover, the larger question of the appropriate conduct of church-state relations in a democratic system is considered. One of the main conclusions that could be drawn from this study is that a presence of a strong religious institution does not necessarily hinder democracy. Instead, cooperation between the church and state is acceptable, and even desirable, as long as two conditions are met. First, all citizens must be guaranteed full religious freedom. Second, the dominant religious institution cannot impose its version of the 'good life' on the rest of society.
Keywords: Political Science; Political Science